Kick it up a notch: Notch signaling and kidney fibrosis - Sweetwyne, Mariya T (Kidney Int Suppl (2011), 2014)
Notch is a critical regulator of kidney development, but the pathway is mostly silenced once kidney maturation is achieved. Recent reports demonstrated increased expression of Notch receptors and ligands both in acute and chronic kidney injury. In vivo studies indicated that Notch activation might contribute to regeneration after acute kidney injury; on the other hand, sustained Notch expression is causally associated with interstitial fibrosis and glomerulosclerosis. This review will summarize the current knowledge on the role of the Notch signaling with special focus on kidney fibrosis.